Enhancing Social Connectedness And Emotional Awareness: A Comprehensive Intervention Study Investigating The Impact Of Psychoeducation On Parents Of Children With Autism Spectrum Disorder - Aneela Begum , Maryam Kausar , Allah Nawaz , Aafra Zeb , Wakqas Khalid Ally , Mehreen Khalid , Afroz Ahmad (Migration Letters, 2024)
Background: Parents having Autistic children often experience social disconnection from others because of their child’s autism-related behaviors. They distance themselves from friends and relatives, and occasionally, others stop them from participating in[1] social gatherings and activities. The purpose of this research is to increase the knowledge and comprehension of social workers and other professionals working in the sector, as well as to empower families whose children present with Autism spectrum disorder (ASD) through psychoeducation. Objective: Examining how psychoeducation affects emotional awareness and social connectedness in parents having Autistic children. Method: The participants of the study were 50 mothers of children who were already diagnosed with ASD. They were divided into two groups (treatment group = 35, control group = 15). The study comprised a total of three phases. In 1st phase, a pre-test assessment was carried out, and data regarding Alexithymia and social connectedness was collected using the Perth Alexithymia Questionnaire (PAQ) (Preece et al., 2018) and Social Connectedness Scale (SCS) (Lee & Robbins, 1995) from total 50 mothers of diagnosed ASD children. In 2nd phase, psychoeducation intervention was conducted on mothers (n=35). In the third phase, the post-test assessment was carried out. Results: Regarding the overall pre and post intervention values of PAQ value (102.04 ± 7.23 vs. 81.21 ± 10.35) and SCS value (17.92 ± 2.58 vs. 24.56 ± 3.13: p <0.001), there were significant differences in the treatment group, but not in the control group (p>0.05). Psychoeducation significantly influenced parents with weaker social connections and Alexithymia. Summary/Conclusion: There is a decrease in Alexithymia and an increase in social connectedness in Parents of Autistic children after psychoeducation intervention.